2009
DOI: 10.1007/dcr.0b013e3181a8fbb7
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Complex Anal Fistulas with the Anal Fistula Plug: A Prospective, Multicenter Study

Abstract: Because there is still no standard for the treatment of high transsphincteric fistulas and because recurrence rates are high for all procedures performed, new techniques are needed for this complex disease. Our success rate of 62% is promising because this technique can be used as a first approach to close the fistula tract without destruction of the sphincter muscle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(45 citation statements)
references
References 21 publications
3
39
1
2
Order By: Relevance
“…25 Conversely, a randomized trial of the anal fistula plug vs the endorectal advancement flap was closed prematurely when 12 of 15 patients had a recurrence with the fistula plug at 1-year follow-up. 26 These 2 studies again demonstrate the wide range of results reported for the fistula plug.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Conversely, a randomized trial of the anal fistula plug vs the endorectal advancement flap was closed prematurely when 12 of 15 patients had a recurrence with the fistula plug at 1-year follow-up. 26 These 2 studies again demonstrate the wide range of results reported for the fistula plug.…”
Section: Discussionmentioning
confidence: 99%
“…Last, Hirschburger and colleagues identify smoking and diabetes as risk factors for plug failure. 25 These factors were not tracked in the current study. Future plug studies should seek to clarify the association of successful closure and tract length with respect to sphincter involvement, smoking, and diabetic status.…”
Section: Discussionmentioning
confidence: 99%
“…It represents the first minimally invasive alternative to formal fistula-inano surgery, recommended as a first line intervention for simple fistula-in-ano. [6][7][8] Innovators from the US have already described the use of the Surgisis ® anal fistula plug as a minimally invasive therapy for the management of fistulas not in the perineum. Wood et al described the successful closure of a solitary persistent gastrocutaneous fistula following removal of a PEG tube with a porcine fistula plug 9 and Paul et al describe similar success closing a solitary bronchopleural fistula following a partial pneumonectomy.…”
Section: Discussionmentioning
confidence: 99%
“…It is now thought that mechanical debridement of the tract is necessary for good plug incorporation, especially since literature suggests that at least some anal fistula tracts may be epithelialized [21]. Furthermore, other authors have advocated the widening of the external opening following placement of the plug to ensure adequate drainage and prevent abscess formation [22]. While we mobilized a small flap of mucosa over the head of the plug to ensure that the plug was completely buried under the rectal mucosa, this practice was not routinely recommended at the time the study commenced.…”
Section: Discussionmentioning
confidence: 99%